Likely impact of the UN Convention on disability on mental health services. Issue 4 (July 2017) - Jahn, Ina; Becker, Thomas; Stengler, Katarina
Abstract : Purpose of review: After a large majority of UN member states ratified the Convention on the Rights of Persons with Disabilities (UNCRPD), this article aims to provide an overview of its implementation and possible effects in the area of mental health services in individual contract states. Recent findings: This article looks at the implementation processes of the UNCRPD in individual industrialized, emerging and developing countries. In addition to changes in national legislation, potential influences on the supply and support systems for persons with mental illness are considered. Positive approaches and efforts are described. Difficulties and barriers that could be responsible for the long process of implementation of the UNCRPD are described, and so is the restructuring and development of adequate supply and support systems in the area of mental healthcare in industrialized, emerging and developed countries. Summary: The UNCRPD is a groundbreaking encouragement for various changes in the area of mental health services. The path to subject orientation and individual support structures is long and slow in all countries – in industrialized, emerging and developed countries. National law and health legislation must be adjusted and developed to create an obligatory context for inclusive services required for persons with mental illnesses. Community-based care is prioritized, and this facilitates participation and inclusion.